2018
DOI: 10.1155/2018/7584736
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Clinical Characteristics and Etiological Factors in Children with Molar Incisor Hypomineralization

Abstract: Aim The purpose of the present study was to evaluate the clinical defects and etiological factors potentially involved in the onset of MIH in a pediatric sample. Methods 120 children, selected from the university dental clinic, were included: 60 children (25 boys and 35 girls; average age: 9.8 ± 1.8 years) with MIH formed the test group and 60 children (27 boys and 33 girls; average age: 10.1 ± 2 years) without MIH constituted the control group. Distribution and severity of MIH defects were evaluated, and a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
0
4

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 18 publications
4
19
0
4
Order By: Relevance
“…Besides that, MIH-affected patients present other several clinical problems such as esthetic complains, loss of fillings, need of reinterventions, an increased risk of dental caries, and dental hypersensitivity [Giuca et al, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, MIH-affected patients present other several clinical problems such as esthetic complains, loss of fillings, need of reinterventions, an increased risk of dental caries, and dental hypersensitivity [Giuca et al, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…Some of theseinclude low birth weight, chicken pox, hypocalcaemia, oxygenation issues, and fever in early childhood. 3 However, many studies in literature could not find significant relation between these factors and the disorder. Yet a study conducted in Brazil 5 found that oxygenation at birth, pneumonia, asthma, bronchitis, hospitalization and use of antibiotics had significant relation with molar incisor hypomineralization.…”
Section: Introductionmentioning
confidence: 99%
“…It was firstly named as molar incisor hypomineralization in 2001, suggested by Weerheijm et al 1 Molar incisor hypomineralization is defined as a developmental disorder that involves at least one permanent first molar by opacities that are not symmetrical. [2][3][4][5] The prevalence of molar incisor hypomineralization varies in different regions of the World and it was found in literature that lowest frequency of molar incisor hypomineralization is in Chinese population. 6 Studies conducted in Germany, Spain, Iran, Brazil and Iraq 7 found prevalence of molar incisor hypomineralization between 10.15 to 21.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, a pesar de que existe una clasificación y criterios diagnósticos para el HIM, un gran número de odontólogos confunde el diagnóstico diferencial entre la alteración del esmalte versus lesiones cariosas [10][11][12][13] . Esto a su vez, genera un inadecuado plan de tratamiento, el cual conlleva al fracaso de la restauración debido a un diagnóstico equivocado [14][15] De igual manera, es importante resaltar las dificultades a las que se enfrenta el odontólogo al realizar el tratamiento en la pieza 16 . Entre estas se encuentran: manejar la conducta del niño, realizar un Odontol Pediatr Vol 14 Nº 2 Julio -Diciembre 2015 adecuado nivel de anestesia, elegir un buen diseño de preparación cavitaria y seleccionar apropiadamente los materiales de restauración [17][18] .…”
Section: Introductionunclassified